FACTORS AFFECTING AUDIT DELAY IN BANKING COMPANIES IN INDONESIA - Anggoro Sugeng; Asmi Trisna Puspita; Ku Abdul Muhaimin Yusof (IAIN Manado, 2021)
This study aims to determine the factors that cause audit delay in banking companies listed on the Indonesia Stock Exchange. The variable that distinguishes this research from the others is the audit committee variable as a new indicator. Overall, there are 5 assessment indicators in this study consisting of firm size variable, company profit/loss variable, auditor opinion variable, audit committee variable, and KAP size variable. The population consists of banking companies in Indonesia that are listed on the Indonesia Stock Exchange with a sample of 30 companies with a sampling technique of purposive sampling. The analysis used in this study is multiple linear regression analysis, which is in the form of panel data. This study indicates that the variables of KAP size and company profit/loss have a significant effect on audit delay. While the variables of the audit committee, auditor's opinion, and firm size have no significant effect on audit delay.